2021
DOI: 10.3390/su132313066
|View full text |Cite
|
Sign up to set email alerts
|

Design, Implementation, and Evaluation of an Immersive Virtual Reality-Based Educational Game for Learning Topology Relations at Schools: A Case Study

Abstract: Education has always been modified by employing different technologies to enhance the knowledge acquisition and performance of students. Virtual Reality (VR) along with the Game Industry is among those evolving technologies for educational applications. This study aimed to design, implement, and evaluate an immersive VR-based Educational Game (IVREG) for learning topology relations. Topology relations are one of the fundamental topics which exist in Geospatial Information Science (GIS); due to the great capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Four papers by the same lead author explored the incorporation of video games into the curricula of secondary education courses (Annetta et al, 2009a(Annetta et al, , 2009b(Annetta et al, , 2010(Annetta et al, , 2013. Another four papers (Cheng et al, 2015;Safari Bazargani et al, 2021;Virvou & Katsionis, 2008;Yuana et al, 2015) explored virtual reality gaming in secondary education. Virtual reality is a constructed environment that provides a sense of presence for users in a real or imaginary world (Manis & Choi, 2019).…”
Section: Primary and Secondary Education-level 2 Cluster 1 Sub-clustermentioning
confidence: 99%
“…Four papers by the same lead author explored the incorporation of video games into the curricula of secondary education courses (Annetta et al, 2009a(Annetta et al, , 2009b(Annetta et al, , 2010(Annetta et al, , 2013. Another four papers (Cheng et al, 2015;Safari Bazargani et al, 2021;Virvou & Katsionis, 2008;Yuana et al, 2015) explored virtual reality gaming in secondary education. Virtual reality is a constructed environment that provides a sense of presence for users in a real or imaginary world (Manis & Choi, 2019).…”
Section: Primary and Secondary Education-level 2 Cluster 1 Sub-clustermentioning
confidence: 99%
“…Huang et al [23] concluded that medium and high-level immersion can stimulate learning motivations, participation in, and support of learning. Bazargani et al [24] stated that the HMD VR-based learning method contributes to a higher immersion level than the tablet PC-based method. Cheng's [25] research shows that students' learning motivations can be significantly regulated by their immersion-type attention and enjoyable experience.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The most effective and practical work is introducing new educational approaches including artistic, abstract or design works and games to the curriculum where students have time to do so and discuss it with each other in schools. This can be carried out by integrating educational concepts in 3D computer-aid or virtual reality systems that provide a rich environment for students to play and reinforce SI such as ref (100,101) or hands-on concrete materials (e.g., puzzle pieces, blocks, origami) such as ref (102). Project-based learning is a useful approach where students gain experience and knowledge about solving real-world problems and challenges, as has been recommended in many studies (103).…”
Section: Implementation To Improve Educationmentioning
confidence: 99%